The relationship between inorganic ion composition of saliva and dental caries prevalence in children - Hiraishi, N; Tanaka, M; Takagi, Y (Kōkūbyō Gakkai Zasshi, 1999)
In order to know the relationship between inorganic ion composition of saliva and dental caries prevalence, saliva from children was studied. The saliva samples were collected from 30 subjects aged 3 to 18 years. Each inorganic ion concentration and pH of saliva was measured and their relationship to dental caries was studied. The results were as follows: 1. Significant relationship was noted between ammonium ion concentration and caries prevalence. It was suggested that the ammonium ion was derived from decomposition of urea or amino acids. 2. Although a significant relationship was also noted between potassium ion concentration and caries prevalence, its direct process is unknown. 3. The sodium ion concentration in saliva increased with age, which implies its relationship to the development of the hormonal system.